Automatic detection temperature transmitter for calibration process using RTD - Mustaqim, Hazmi (2010)
The purpose for this project is to detect temperature for Calibration Process using Resistive Thermal Device (RTD) automatically. This project will be used Visual Basics (VB) programmed to develop Graphical User Interface (GUI). An RTD will be use as temperature sensor in this Calibration Process. The software and the temperature sensor will be interfaced by using a Data Acquisition (DAQ) card. Proportional–Integral–Derivative (PID) controller will be purpose for automatic detection for temperature system. The expected result for this project is an automatic detection system for temperature measure during the Calibration Process. The accuracy of the measurement will be monitor beside the analysis of uncertainty and confidence limit